ISLAM: NEGARA, DEMOKRASI, HUKUM DAN POLITIK - Zuhraini, Zuhraini (Analisis: Jurnal Studi Keislaman, 2014)
ISLAM  : STATE,  POLITICS,  AND  DEMOCRACY.  Islam,  as a comprehensive religion, does not recognize the dichotomy between religion and the state, politics, and democracy. As a religion,  Islam possesses  universal  doctrines  on  the  matter  of state,  politics  and democracy  which  also  become  parts  of thead-din  al-Islami.  As  part of  the  phenomenon  of  civilization, culture and Islamic values are developed to be in tune with the social institutions affected by the situation  and the dynamics of space and time. histrorical  and socio-cultural  factors and socio- Muslims also have an effect on the analysis and understanding of the universal teachings. The emergence of differences in analysis of a variety of state and political issues is caused by such different interpretations (polyinterpretable) which, finally, influences the formulation  of political  thoughts  and practices  in contemporary Muslim countries. This article tries to open up minds that Islam is not merely a ritual religion which contains  a set of doctrines, but it also possesses a holistic, universal, and systematic   views toward worldly life.